Risk factors for non-fatal myocardial infarction in young South Asian adults. Issue 3 (13th February 2004) - Ismail, J; Jafar, T H; Jafary, F H; White, F; Faruqui, A M; Chaturvedi, N
Abstract : Objective: To determine the risk factors for premature myocardial infarction among young South Asians. Design and setting: Case–control study in a hospital admitting unselected patients with non-fatal acute myocardial infarction. Methods and subjects: Risk factor assessment was done in 193 subjects aged 15–45 years with a first acute myocardial infarct, and in 193 age, sex, and neighbourhood matched population based controls. Results: The mean (SD) age of the subjects was 39 (4.9) years and 326 (84.5%) were male. Current smoking (odds ratio (OR) 3.82, 95% confidence interval (CI) 1.47 to 9.94), use of ghee (hydrogenated vegetable oil) in cooking (OR 3.91, 95% CI 1.52 to 10.03), raised fasting blood glucose (OR 3.32, 95% CI 1.21 to 8.62), raised serum cholesterol (OR 1.67, 95% CI 1.14 to 2.45 for each 1.0 mmol/l increase), low income (OR 5.05, 95% CI 1.71 to 14.96), paternal history of cardiovascular disease (OR 4.84, 95% CI 1.42 to 16.53), and parental consanguinity (OR 3.80, 95% CI 1.13 to 1.75) were all independent risk factors for acute myocardial infarction in young adults. Formal education versus no education had an independently protective effect on acute myocardial infarction (OR 0.04, 95% CI 0.01 to 0.35). Conclusions: Tobacco use, ghee intake, raised fasting glucose, high cholesterol, paternal history of cardiovascular disease, low income, and low level of education are associated with premature acute myocardial infarction in South Asians. The association of parental consanguinity with acute myocardial infarction is reported for the first time and deserves further study.